1992
DOI: 10.1002/jez.1402610208
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in shark testicular structure and spermatogenesis

Abstract: In this report, seasonal changes in testicular structure and spermatogenesis in several shark species are reviewed, and new information concerning the bonnethead shark, Sphyrna tiburo, is presented. Shark species are separated into four categories based on the relationship between testicular GSI and mating season: 1) species that have a defined seasonal cycle in GSI and a defined mating season, 2) species that have a defined seasonal cycle in GSI and that mate year-round, 3) species that show no seasonal chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
64
1
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 23 publications
14
64
1
2
Order By: Relevance
“…Even though, the observations made in this study correspond only to two seasons, these are in agreement with Parsons & Grier (1992). These authors stated that the definition of the testicular coverage of each stage is a useful tool to determine a seasonal cycle of activity in this group of fish, especially when these data are correlated with mating activity observations and gonadosomatic indexes.…”
Section: Tab I Size and Nuclear Dimensions Of Maturative Spermatogesupporting
confidence: 88%
See 1 more Smart Citation
“…Even though, the observations made in this study correspond only to two seasons, these are in agreement with Parsons & Grier (1992). These authors stated that the definition of the testicular coverage of each stage is a useful tool to determine a seasonal cycle of activity in this group of fish, especially when these data are correlated with mating activity observations and gonadosomatic indexes.…”
Section: Tab I Size and Nuclear Dimensions Of Maturative Spermatogesupporting
confidence: 88%
“…This organization pattern could be interpreted as an adaptation to the "flattened" body of these fish. Parsons & Grier (1992) have analyzed the changes in spermatocysts diameter of Sphyrna tiburo (Linnaeus, 1758), and reported that there was an increase in diameter until the stage of cysts containing secondary spermatocytes. However, in S. bonapartii there was an increase in diameter until the cysts with spermatids, which are the largest ones.…”
Section: Tab I Size and Nuclear Dimensions Of Maturative Spermatogementioning
confidence: 99%
“…In our opinion, it might be connected to individual variability reported among cartilaginous fishes. In the reproductive system of cartilaginous fishes, individual variability has been reported regarding the presence of gonia during the early stage of embryonic development (Beard, 1904), as well as follicle (Mellinger, 1974) and Leydig cells distribution, data that support the concept of "reproductive plasticity" expressed by Parsons and Grier (1992). Such a variability is extremely important as it would represent the variation targeted by natural selection, and it may possibly account for the different reproductive strategies adopted by cartilaginous fishes.…”
Section: Discussionmentioning
confidence: 90%
“…Garnier and Sourdaine (1990) have observed a rise in sperm production, from March to May and in August, when compared to the rest of the year. Finally, in S. tiburo, spermatogenesis begins in May or June and spermatocysts containing spermatozoa are observed in August (Parsons and Grier, 1992).…”
Section: Testicular Structurementioning
confidence: 98%